2002
DOI: 10.1002/etc.5620210606
|View full text |Cite
|
Sign up to set email alerts
|

Assessing relationships between human land uses and the decline of native mussels, fish, and macroinvertebrates in the Clinch and Powell river watershed, USA

Abstract: The free-flowing Clinch and Powell watershed in Virginia, USA, harbors a high number of endemic mussel and fish species but they are declining or going extinct at an alarming rate. To prioritize resource management strategies with respect to these fauna, a geographical information system was developed and various statistical approaches were used to relate human land uses with available fish, macroinvertebrate, and native mussel assemblage data. Both the Ephemeroptera, Plecoptera, Trichoptera (EPT) family-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Past research has shown that both pasture and suburban/urban landuses can have substantial sediment loadings into streams (Wahl et al. , 1997; Diamond et al. , 2002; Richardson and Jowett, 2002; Riley et al.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that both pasture and suburban/urban landuses can have substantial sediment loadings into streams (Wahl et al. , 1997; Diamond et al. , 2002; Richardson and Jowett, 2002; Riley et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although the above water and sediment quality constituents have been monitored in the Clinch River by government agencies for several decades, the resulting water and sediment quality data had not been analyzed previously for freshwater mussel conservation purposes. Prior studies have cited a variety of water environmental factors, including land use influences and contaminated water and sediments, as priority stressors for mussels in the Clinch River (Diamond and Serveiss, ; Diamond et al ., ; Locke et al ., ). However, which stressors and/or stressor‐source watershed activities have contributed most substantially to mussel populations' historic declines is not known; nor is it known which (if any) historic stressors remain as significant current threats.…”
Section: Introductionmentioning
confidence: 97%
“…Several competing hypotheses have been posed to explain spatial and temporal patterns of decline and persistence in the Clinch River. These hypotheses include, but are not limited to, water‐quality degradation caused by current coal and gas extraction, pollutants present in sediments from past energy extraction, changes in land use or land cover, water quality degradation from agricultural practices, episodic acute chemical spills, presence of coal fines in habitats occupied by mollusks, and physical degradation of local habitat (Diamond et al ., ; Van Hassel, ; Krstolic et al ., ; Johnson et al ., ; Jones et al ., ). Several of these hypotheses are explored elsewhere in this series of articles and in supporting documents (Krstolic et al ., ; Johnson et al ., ; Price et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Confounding abiotic and biotic factors acting at several spatial and temporal scales likely shape mussel assemblages. Several researchers have linked catchment‐scale land use, underlying geology, and soil type to richness and abundance (Arbuckle and Downing, ; Diamond et al ., ; McRae et al ., ; Poole and Downing, ). Others have found that abundance is associated with local channel geomorphology (Vannote and Minshall, ; Church, ; Howard and Cuffey, ; McRae et al ., ; Stone et al ., ; Gangloff and Feminella, ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation